Evaluating the influence of time of day on activity engagement in persons with dementia. (6th November 2019) - Boyden, Darienne E.; Miltenberger, Raymond G.; Novotny, Marissa A.
Abstract: Dementia is a serious disease affecting a growing number of people. With the onset of dementia comes a decline in social activity engagement that can negatively impact multiple aspects of a person's life. Research suggests that time of day may influence a person with dementia's behavior, including activity engagement, but such research is limited. The purpose of this study was to evaluate the influence of time of day on engagement in activities in persons diagnosed with dementia. An alternating treatments design was used with three participants to measure activity engagement during two times of day, morning and afternoon, and during two activities, a moderately preferred and a low preferred. Results showed no differentiation in engagement between morning and afternoon activities for all three participants, with high levels of engagement during both times of day. For two participants, results showed no differentiation in engagement between moderately preferred and low preferred activities. For one participant, levels of engagement were higher during moderately preferred activities than during low preferred activities.